2021
DOI: 10.1177/07334648211018299
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Stewardship Interventions to Optimize Treatment of Infections in Nursing Home Residents: A Systematic Review and Meta-Analysis

Abstract: Effects of antibiotic stewardship program (ASP) interventions to optimize antibiotic use for infections in nursing home (NH) residents remain unclear. The aim of this systematic review and meta-analysis was to assess ASPs in NHs and their effects on antibiotic use, multi-drug-resistant organisms, antibiotic prescribing practices, and resident mortality. Following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, we conducted a systematic review and meta-analysis using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
0
8
0
1
Order By: Relevance
“…42 support algorithms, particularly for UTIs, were the most effective. 43 Sadly, another systematic review found that evidence for electronic clinical decision support in NHs is observational and limited in quality. 44 Electronic clinical decision supports represents an untested but promising path forward to address decision-making deficits in NH clinicians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 support algorithms, particularly for UTIs, were the most effective. 43 Sadly, another systematic review found that evidence for electronic clinical decision support in NHs is observational and limited in quality. 44 Electronic clinical decision supports represents an untested but promising path forward to address decision-making deficits in NH clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Research in other clinical settings such as hospitals demonstrates that clinical decision support improves the diagnosis of infections and antibiotic prescribing, 40,41 including point‐of‐care clinical decision support, with moderate success 42 . A systematic review of NH antimicrobial stewardship interventions found that educational efforts and clinical decision support algorithms, particularly for UTIs, were the most effective 43 . Sadly, another systematic review found that evidence for electronic clinical decision support in NHs is observational and limited in quality 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobials are often used in the residents who do not meet clinical criteria for UTI in the nursing homes [34]. Nursing homes with more occupied beds and higher number of admissions might have a higher rate of inappropriate use of antimicrobials and the interventions of ABS might help improve the treatment of infections for the residents in the nursing homes [35]. The application of ABS might improve the nursing quality in these nursing homes with large numbers of occupied beds and admissions.…”
Section: Discussionmentioning
confidence: 99%
“…Improving antibiotic use in the care of the institutionalized elderly in order to protect residents and reduce the threat of antibiotic resistance is a global priority. The Centers for Disease Control (CDC) and others recommends that all nursing homes take steps to improve antibiotic prescribing practices and reduce inappropriate antibiotic use [7][8][9][10].…”
Section: Is It Necessary For Each Ltcf To Have a Physician Or Nurse R...mentioning
confidence: 99%